Developing A Scale Of Financial Attitudes In Emergency Fund Ownership Decision Making - Ade M. Adiandari; Bambang Sumintono; Yuliani (Jurnal Manajemen, 2022)
Financial attitudes in emergency fund ownership decision-making are important in shaping decision-making behaviour to have an emergency fund. In order to obtain an accurate profile of financial attitudes in emergency fund ownership decision-making, it required a good instrument with a precise measurement model. This study focuses on developing a financial attitude scale in emergency fund ownership decision-making using Rasch model. The participants were 106 respondents and after going through 2 analysis process stages using Winsteps, the instruments possessed a very decent reliability index, both from alpha Cronbach's and item reliability value. The items have also met the accuracy of the item model, the unidimensionality number was above the standard, as well as the unexplainable variance by the instruments did not exceed the standard. Overall, it can be concluded that the financial attitude scale in emergency fund ownership decision-making held a decent psychometric attitude so this attitude scale can be used to a second stage pilot test process with a larger number of respondents.